(untitled) (Research, Society and Development, 2021)
Care for onco-hematological clients should be planned in a continuum that considers their family system as an important element for the management of chronic health conditions. Thus, this study aims to identify the demands for supported self-care present in the family system of the onco-hematological client. This is a qualitative study carried out through semi-structured interviews with four family systems of onco-hematological clients of a university hospital based on a script elaborated with questions regarding the functional category of the Calgary Model of Family Assessment and the evaluation item of the 5 “A” methodology of the Supported Self-Care Manual. After analyzing and interpreting the data, a thematic unit with three subunits was obtained, which were guided by the NANDA domains and classes to identify the affected domain and its respective focus of attention: 1 - decision making from the family system; 2 - (re) organization and family involvement after the impact of the diagnosis; and 3 - well-being and co-responsibility for health control. It is concluded that the family reorganizes itself in order to restore the health of its relative, requiring care that involves counseling, support and health promotion; pointing to the need to expand the use of the references of this study in nursing care for the family of the onco-hematological client.